The Impact of Sharia Policy On Libyan Legislation in Combating Corruption Crimes (Al-Mukhtar Journal of Legal Science, 2024)
The goal of this  study is to explain what islam had come of guarantees  which constiutes  community from corruption، and to  find-out the precautionary measures which the islamic legislative  performed  ، inorder to   put an end to the phenomenon of corruption and  not to obey what god oredred with ، and to abandoning islamic values ​​such as integrity، honesty، truthfulness، justice and transparency, begenning from the protection methods from corruption  which is represented in reforming the creed and intensifying the discourse of encouragement for integrity and intimidation from corruption and its consequences، in addition to legislating penalties and holding accountable anyone who commits the crime، whether in libyan criminal legislation or in the system of oversight bodies specialized in combating corruption in libya ، and the range of texts compatibility in the libyan legislation to coincide with the islamic legislation rules . and explaining the similarities and differences between themin combatig corruption crimes   which it is eating away at the body of the nation and is getting worse until it has reached critical levels، where society is threatened with collapse.
Keywords: Sharia and law; Precautionary measures; Regulatory bodies; Anti-corruption; Crimes and punishments